A BIT goes a long way: Bilateral investment treaties and cross-border mergers - Bhagwat, Vineet; Brogaard, Jonathan; Julio, Brandon (Journal of Financial Economics, 2021)
We examine whether bilateral investment treaties (BITs), an external governance mechanism, stimulate cross-border mergers by protecting the property rights of foreign acquirers. Exploiting the staggered adoption and bilateral nature of the treaties, we find that BITs have a large positive effect on cross-border mergers. The probability and dollar volume of mergers between two given countries more than doubles after the signing of a BIT. The increase is driven by deals flowing from developed economies to developing economies and is concentrated in target countries with medium levels of political risk. The results suggest BITs are effective in expanding the global market for corporate control, particularly in the developing world.